Violência, clima social escolar e síndrome de Burnout em docentes - Cardoso, Evandra (Universidade do Vale do Rio do Sinos, 2009)
This paper is part of the Clinical Research of Childhood and Adolescence, of the Graduate Syllabus in Psychology – Master’s degree of the University of Vale do Rio dos Sinos-UNISINOS. This paper is divided into three parts. The first is in the wording of an article for review, as rescue theoretical issues about the study, involving Burnout Syndrome, social climate and school violence. The second is an empirical study presented in order to contribute to the field of approaches on the Burnout Syndrome in teachers. Finally, a report detailing the experience of the researcher as a whole is presented. This study tried to evaluate the levels of burnout among 135 teachers from public schools, investigating the relationship between their perceptions of social climate and school violence. It uses a quantitative research approach in which tools as Inventory MBI - Maslach Burnout Inventory Maslach & Jackson, as ED-Educators Survey, which will narrow the Burnout Syndrome in teachers, was employed . The scale ECLIS - Scal
Keywords: docente; Burnout; teachers; social climate; Ciências Humanas